Project-Based Learning Based on Stem (Science, Technology, Engineering, and Mathematics) Enhancing Students Science Knowledge Competence - Putu Lely Somya Prabawati; Gusti Ngurah Sastra Agustika (Universitas Pendidikan Ganesha, 2020)
Student scientific literacy is still low categorized. One of the reasons is that students are memorizing natural science (IPA) materials, which result in poor understanding of science concepts. This study examines the effectiveness of the STEM Oriented Project Based Learning model for elementary science knowledge competencies. This type of research is a Quasi-experiment using Nonequivalent Control Group Design. The study population was fifth-grade elementary school students, 209 students. This study uses two sample groups, the experimental group, and the control group. The research sample was obtained through random sampling techniques and had passed the equality test. The experimental group in this study amounted to 33 students, and the control group was 30 students. Data were collected using an ordinary multiple-choice objective test and then analyzed by polled variance t-test. The data analysis results showed that t = 2,237> t table = 2,000, with a significance level of 5% and dk = 61 so that H0 was rejected. It means that there is an influence of science knowledge competence between the experimental and control groups. Applying the STEM-oriented project-based learning model can make students more motivated to learn to make it easier to understand science materials.